PENGARUH REMUNERASI DAN MOTIVASI TERHADAP KINERJA DI LEMBAGA PEMASYARAKATAN TERBUKA KELAS II B PASAMAN, KAB. PASAMAN BARAT - Endang Tirtana Putra; Abdi Rezki (Jurnal Apresiasi Ekonomi, 2020)
This study applies multiple linear regression analysis with the SPSS Version 16.0 program. To get estimate and good interpretation of this study, the samples studied are set to 32 respondents. Data are collected through a questionnaire to measure quantitative variables with a Likert scale. The results of this study show that there is a relationship between independent variables on dependent variable, and it can be explained that: (1) Remuneration variable does not have significant impact on employee performance, with a regression coefficient of 0.181 and significant rate 0.104 (> 0.05). (2) Motivation variable has significant impactt on employee performance with a regression coefficient of 0.559 and significant rate 0,000 (<0.05). (3) Independent variables simultaneously have significant impact on employee performance with regression coefficient of 1.094 and significant rate 0.000 (<0.05). R² value shows 0.589 or 58.9%. Employee performance variable is affected by Remuneration and Motivation Variables and the remaining 41.1% is affected by other variables.Keywords : Remuneration, Motivation and Performance